‘n Stormkompas in tye van aanpasbare verandering – kontoere van missionêre leierskap - Niemandt, Cornelius J. P. (Verbum et ecclesia, 2008)
A compass in the storms of adaptive change - outlines on missional leadership. The article describes outlines of and elaborates on missional leadership in the challenging times of adaptive change. The insights of Roxburg & Romanuk (2006) and Van Gelder (2007), especially in terms of their contributions on Spirit-led missional leadership, serves as partners for the discussion. This is enriched by other publications and highlighted by the influence of prof Piet Meiring’s life as missional leader. The article describes missional leadership as: • a journey directed by spiritual discernment, • Biblical imagination to discern God’s preferred future, • the art of listening, • the cultivation of an environment that discerns God’s activities among the congregation and in its context, • communally orientated and network-leadership, • cultural transformation, • storytelling, and • taking risks.